Worth seeing but not going to see: Tourism bid must first pass "the Johnson test". Issue 6 (11th May 2015) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – In a review of how cities and other urban centers market themselves in their attempts to benefit from visitors, a five-variable model of purposeful urban destination marketing is presented, concluding that "good" in urban destination marketing is atypical and currently in Europe is confined to only a handful of cities. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.